Haunting Heritage in an Enchanted Land: Magic, Materiality and Second World War German Material Heritage in Finnish Lapland - Herva, Vesa-Pekka (Journal of Contemporary Archaeology, 2015)
This article addresses the functions and meanings of Second World War German material heritage in northern Finland from a haunting perspective and in terms of magical thinking. While archaeologists and heritage professionals have primarily been interested in the historical information that Second World War sites and military material culture may contain, this article explores how encounters and engagements with Second World War materialities in the northern wilderness of Lapland can be considered to affect people and manipulate their perceptions, awareness and understanding of the surrounding world. Second World War sites and matériel may be taken to promote a kind of magical consciousness which enables a degree of restructuring of relationships between the self and world and the past and present.